2019
DOI: 10.1111/gcb.14574
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem carbon response of an Arctic peatland to simulated permafrost thaw

Abstract: Permafrost peatlands are biogeochemical hot spots in the Arctic as they store vast amounts of carbon. Permafrost thaw could release part of these long‐term immobile carbon stocks as the greenhouse gases (GHGs) carbon dioxide (CO2) and methane (CH4) to the atmosphere, but how much, at which time‐span and as which gaseous carbon species is still highly uncertain. Here we assess the effect of permafrost thaw on GHG dynamics under different moisture and vegetation scenarios in a permafrost peatland. A novel experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 126 publications
(226 reference statements)
0
42
0
Order By: Relevance
“…Higher CH 4 oxidation in thawed permafrost versus intact permafrost has also been observed in polygonal tundra (Vaughn et al, 2016) and a peat plateau (Voigt et al, 2019); however, in both cases permafrost thaw led to drier conditions (i.e., less reducing environment). By contrast, our results indicate that more reducing conditions coincide with greater CH 4 oxidation rates.…”
Section: Redox Potential Is a Stronger Predictor Of Methane Oxidationmentioning
confidence: 82%
See 1 more Smart Citation
“…Higher CH 4 oxidation in thawed permafrost versus intact permafrost has also been observed in polygonal tundra (Vaughn et al, 2016) and a peat plateau (Voigt et al, 2019); however, in both cases permafrost thaw led to drier conditions (i.e., less reducing environment). By contrast, our results indicate that more reducing conditions coincide with greater CH 4 oxidation rates.…”
Section: Redox Potential Is a Stronger Predictor Of Methane Oxidationmentioning
confidence: 82%
“…Thus, as permafrost is thawing due to atmospheric warming at a global scale (Olefeldt et al, 2016;Turetsky et al, 2019), it is vital to understand the potential of MOB to attenuate CH 4 emissions from thawing permafrost. Previous work comparing the abundance/activity of MOB using intact and thawed sites (Liebner & Wagner, 2007;Vaughn et al, 2016) or through in vitro experiments thawing permafrost cores (Mackelprang et al, 2011;Voigt et al, 2019) suggests that permafrost thaw can increase CH 4 oxidation. However, these studies focused on comparing end-member thaw states, which omit CH 4 oxidation in transitional thaw stages that can cover a considerable area of thawing permafrost peatlands (Malmer et al, 2005;Palace et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To assess the effect of permafrost thaw on peatland C and N budgets, we distinguish four main potential stages in the longterm transition from stable permafrost to nonpermafrost peatlands ( Fig (45)(46)(47). If thaw progresses into ice-rich permafrost, thermokarst may occur (18).…”
Section: Resultsmentioning
confidence: 99%
“…1) Intact permafrost peatlands are sinks of CO 2 and have near-neutral CH 4 and N 2 O balances ( 41 44 ). 2) Gradual active layer warming and deepening cause releases of CO 2 and N 2 O from the active layer and from newly thawed peat while CH 4 remains near neutral ( 45 47 ). If thaw progresses into ice-rich permafrost, thermokarst may occur ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…There has been considerable interest in quantifying GHG fluxes from high latitude regions; however, most studies concentrate on CO 2 fluxes (Fahnestock et al 1999;Johnson et al 2000;Hobbie et al 2002;Elberling 2003Elberling , 2007Welker et al 2004;Oberbauer et al 2007;Euskirchen et al 2017). Investigations of CH 4 exchange in Arctic ecosystems have often focused on wetland areas (e.g., Mastepanov et al 2013;Olefeldt et al 2013;Johnston et al 2014;Voigt et al 2019) and found fluxes to be dependent mostly on water table position and soil temperature (Christensen 1993;Torn and Chapin 1993;Rustad et al 2001;Brummell et al 2012;Zona et al 2016;Taylor et al 2018;Voigt et al 2019). In wet sites, aboveground biomass can mediate CH 4 emissions by acting as a conduit for gas exchange between the land and the atmosphere (Torn and Chapin 1993;Wilson and Humphreys 2010).…”
Section: Introductionmentioning
confidence: 99%